Atypical Parkinsonism-A Masked Face: Case Report - Anhar, Safiya; Mannikatti, Pradeep Shankrappa; Dutt, Patre Rachita (Indian Journal of Pharmacy Practice)
Wilson's Disease (WD) is an autosomal recessive disorder involving mutations of the ATP7B gene on chromosome 13, characterized by impaired hepatic copper transport, which results in copper accumulation particularly in the liver and brain. Neurological manifestations such as Parkinsonism can occur in advanced stages of the disease but is rare in pediatric patients. A 10-year-old female presented with complaints of inappropriate laughter and slowness in carrying out daily activities. She also had a history of tremors, rigidity, bradykinesia, and dystonic portray of the neck and upper limbs for 2 months. Neurological examination revealed cogwheel rigidity, resting tremors, facial hypomimia, and dystonic portraying of both upper limbs. The patient had no family history of movement disorders. Laboratory investigations, including low serum ceruloplasmin levels and high 24 hr urinary copper excretion, confirmed the diagnosis of Wilson's disease. Ocular examination revealed the presence of Kayser-Fleischer (KF) rings, a common manifestation of Wilson’s disease. Brain Magnetic Resonance Imaging (MRI) demonstrated characteristic findings of basal ganglia hyper-intensities. The patient was treated with Tab Trihexyphenidyl (THP), Vitamin C and Zinc supplementation for 5 days, following which she was discharged with a comprehensive follow-up plan. This case emphasizes the atypical presentation of Parkinsonism in a pediatric patient with Wilson's disease. It underscores the importance of considering Wilson's disease as a potential etiology in young patients presenting with movement disorders, even in the absence of family history. Early diagnosis and treatment are necessary to prevent irreversible neurological damage. Long-term monitoring and follow-up are necessary to ensure treatment efficacy and prevent disease complications.
Keywords: Wilson’s disease; Hepatolenticular Degeneration; Parkinsonian Disorders; KF rings